Pharmacogenetics of Antiplatelet Drugs. (2002) - Curtin, Ronan; Fitzgerald, Desmond J.
Abstract : Pharmacogenetics refers to the genetic factors that influence the response to a drug, often involving genetic variations in drug metabolizing enzymes. The pharmacogenetics of antiplatelet agents is in its infancy and largely reflects variations in drug targets or related genes. One particular gene variant, the Pl A2 polymorphism of the glycoprotein (GP) IIb/IIIa receptor, is now emerging as a probable determinant of the response to antiplatelet agents including GPIIb/IIIa antagonists. This variant may in part explain the heterogeneity in the response to GPIIb/IIIa antagonists. The Pl A2 genotype appears to be associated with an adverse outcome in patients treated with an oral GPIIb/IIIa antagonist and may be a factor in the observed failure of these agents in unselected populations. However, there are preliminary indications that other antiplatelet agents may have an enhanced effect in Pl A2 subjects. Further clinical trials in particular are required to definitively characterize the pharmacogenetic effect of Pl A2 . Other polymorphisms are also likely to contribute to the pharmacogenetics of antiplatelet agents, but these await investigation.